THE OBJECTIVE OF THIS STUDY IS TO ASSESS THE FEASIBILITY OF CULTIVATING CATFISH USING PONDS IN THE CITY OF MAKASSAR - Parinra, Syam Crisan; Bado, Basri; Hastuti, Diah Retno Dwi (Universitas Muhammadiyah Tangerang, 2025)
As an agricultural endeavour, catfish farming has the potential to thrive with the right conditions. The allocation of land for fishing purposes is one such element. Catfish farming gives locals a chance to feed their families an animal protein source while also helping fisheries development projects succeed. This is a feasible financial option due of the widespread use of ponds. An increasingly common form of fish rearing is the simple act of keeping catfish in a pond. Because pond fish farming is still in its early stages, this provides a good opportunity to assess the potential return on investment. Examining the potential of pond-based catfish farming in Makassar City's Biringkanaya District is the primary objective of this research. We used the accidental sampling method to pick our responders. Internal Rate of Return (IRR), Nett Benefit Cost Ratio (Nett B/C), and Nett Present Value (NPV) are the data analysis approaches that were utilised to process these data.